Fur Color and Nutritional Status Predict Hair Cortisol Concentrations of Dogs in Nicaragua - Bowland, Grace B.; Bernstein, Robin M.; Koster, Jeremy; Fiorello, Christine; Brenn-White, Maris; Liu, James; Schwartz, Laura; Campbell, Amanda; von Stade, Devin; Beagley, Janet; Pomerantz, Julie; González, Alejandro; et al. (Frontiers in Veterinary Science, 2020)
Humans have long possessed an extensive, intimate relationship to the domesticated dog, and cultures around the world today continue to rely on dogs to carry out vital tasks, including hunting, guarding, and transportation. Thus, it is important to understand the dynamics that play into a dog’s ability to carry out human-assigned tasks. Cortisol is a glucocorticoid hormone which plays a critical role in a number of regulatory functions in the body and is often analyzed to assess aspects of health, stress response, and growth and reproduction. Current published research on cortisol in dogs has been relatively limited, leaving a need for larger-scale studies to assess whether current understandings of how cortisol acts in dogs is applicable to dogs within dynamic and heterogeneous environments. This study examines the relationships between hair cortisol concentrations (HCC) and sex, nutritional status (as determined by body condition scores, or BCS), and body mass (geometric mean calculated from morphometric measurements), as well as the potential influence of hair pigmentation (light, dark, or agouti/mixed) on HCC in domesticated Nicaraguan hunting dogs of the Bosawas Biosphere Reserve. The dogs examined in this study live in a marginal environment where disease, malnutrition, and mortality rates are high. For fur color, HCC was significantly higher in light fur than in than dark and mixed fur (p<.001). In addition, BCS scores were found to have a negative effect on HCC (p<.001). In contrast with findings from prior studies, sex exhibited a weak but significant effect, as HCC were on average higher in female dogs (p<0.05). The results of this study confirm previous findings with respect to the relationship between HCC and body size/condition and add new findings of the link between cortisol and body condition scores in dogs, potential sex differences in HCC to the current understanding of physiological and nutritional variables of stress within dogs under varying environmental conditions.